Medieval Universities, Legal Institutions, and the Commercial Revolution - Davide Cantoni; Noam Yuchtman (Center for Economic Studies and ifo Institute (CESifo), 2013)
We present new data documenting medieval Europe's Commercial Revolution using information on the establishment of markets in Germany. We use these data to test whether medieval universities played a causal role in expanding economic activity, examining the foundation of Germany's first universities after 1386 following the Papal Schism. We find that the trend rate of market establishment breaks upward in 1386 and that this break is greatest where the distance to a university shrank most. There is no differential pre-1386 trend associated with the reduction in distance to a university, and there is no break in trend in 1386 where university proximity did not change. These results are robust to estimating a variety of specifications that address concerns about the endogeneity of university location. Universities provided training in newly-rediscovered Roman and canon law; students with legal training served in positions that reduced the uncertainty of trade in the Middle Ages. We argue that training in the law, and the consequent development of legal and administrative institutions, was an important channel linking universities and greater economic activity in medieval Germany.
Keywords: I25; N13; N33; O10; 330; human capital; historical development; legal institutions